Improved Cardiac Proton Magnetic Resonance Spectroscopy at 3 T Using High Permittivity Pads. Issue 2 (February 2016) - de Heer, Paul; Bizino, Maurice B.; Versluis, Maarten J.; Webb, Andrew G.; Lamb, Hildo J.
Abstract : Objective: The aim of this study was to determine whether high permittivity (HP) pads can be used to increase the signal-to-noise ratio (SNR) of cardiac proton magnetic resonance spectroscopy at 3 T, allowing faster data acquisition. Materials and Methods: The institutional review board approved the study protocol, and written informed consent was obtained from all participants. In 22 healthy volunteers, water-suppressed localized spectra were acquired in the interventricular septum without and with HP pads. The SNR and myocardial triglyceride content (MTGC) were measured without and with the HP pads, and the results were compared with a paired sample Student t test. Results: Application of HP pads increased mean (SD) SNR from 27.9 (15.6) to 42.3 (24.4) ( P < 0.0001), a mean gain of 60%. The acquisition time can thereby be reduced from just under 5 minutes to just under 2 minutes while maintaining the same SNR. The mean (SD) MTGC was 0.39% (0.17%) without pads and 0.38% (0.15%) with pads ( P = 0.83) for the healthy volunteers, showing that no bias is introduced by using the pads. No difference in spectral linewidth was measured ( P = 0.80), the values being 17.4 (4.9) Hz without and 17.1 (3.2) Hz with pads. Both transmit and receive maps showed increases in sensitivity due to the presence of the HP pads. Conclusions: High permittivity pads improve cardiac proton magnetic resonance spectroscopy at 3 T by increasing the SNR on average by 60%, which can be used to reduce data acquisition time significantly, allowing fast assessment of MTGC without compromising spectral quality. The SNR increase arises primarily from the increase in receive sensitivity of the phased array, which is more closely coupled to the body via the HP pads. In addition, the transmit efficiency is also increased, allowing shorter or lower power radiofrequency pulses.